High-tech industry development: selection of technology parks operation model elements in the field of high technology - V. V. Degtyareva; M. S. Seregin (Управление)
The article presents the justification of model elements choice for technology parks work in the sphere of high technologies in Russia. The methodology for creating the model, which was built on the position of borrowing the best practices of existing models of innovation infrastructure facilities operation and functioning in the country, has been given. It has been proposed to form a rating among operating technology parks, within the framework of which a comprehensive assessment of technology park management companies’ performance has been carried out according to four groups of indicators (sub-indexes) such as subjects investment attractiveness, information openness, technology parks internal ecosystem, and management company efficiency. Based on the rating results, the leaders among technology parks have been identified, and their behavioral models adopted as reference metrics for the model to be developed. Based on the leaders’ position, it has been proposed to choose the best technology parks model in the field of high technologies in terms of their interaction with residents. Recommendations have been presented for the technology parks infrastructural model as the most promising for private companies, while investment projects should be developed considering federal requirements and standards to ensure their successful implementation and achievement of the set goals. Technology parks in the sphere of high technologies play a key role in Russian economy development. They contribute to the development of innovations, new technologies, high-tech industries, and knowledge-intensive business. It is important that such technology parks development is optimally organized with due regard to modern requirements and regulatory measures.